2021
DOI: 10.2147/cmar.s295833
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0006174 Accelerates Colorectal Cancer Progression Through Regulating miR-138-5p/MACC1 Axis

Abstract: Background Circular RNAs (circRNAs) were reported to be involved in the progression of a variety of cancers, including colorectal cancer (CRC). However, the precise functions and mechanism of circRNAs in CRC have not been elucidated. This study aimed to investigate the effect and mechanism underlying circ_0006174 in CRC. Methods The expression of circ_0006174, microRNA (miR-138-5p) and metastasis associated in colon cancer 1 (MACC1) mRNA was detected by quantitative rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Notably, a recent study reports that circ_0006174 is up-regulated in CRC tissues, and overexpression of circ_0006174 promotes CRC cell proliferation, migration and invasion in vitro, and enhances xenograft tumour growth in BALB/c mice by up-regulating MACC1. 7 This report is similar to the findings of our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Notably, a recent study reports that circ_0006174 is up-regulated in CRC tissues, and overexpression of circ_0006174 promotes CRC cell proliferation, migration and invasion in vitro, and enhances xenograft tumour growth in BALB/c mice by up-regulating MACC1. 7 This report is similar to the findings of our study.…”
Section: Discussionsupporting
confidence: 93%
“…6 Moreover, it is reported that circ_0006174 promotes CRC progression by regulating the miR-138-5p/ MACC1 axis. 7 However, the molecular mechanism by which circ_0006174 exerts its effects has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…circ_0006174 is a circRNA which is transcribed from chromosome chr9:110064315-110068928+. A previous study reports that circ_0006174 is highly expressed in CRC tissues and cells that and circ_0006174 can promotes CRC progression via sponging miR-138-5p and upregulating MACC1 ( 8 ). Another study reports that the exosomal circ_0006174 promotes doxorubicin resistance of CRC cells ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to explore the novel circRNAs which participate in CRC progression, the present study analyzed a microarray dataset (GSE138589) in the Gene Expression Omnibus (GEO) database and identified a circRNA, circ_0006174, which is upregulated in CRC tissues. Some previous studies have reported that circ_0006174 promotes CRC progression and contributes to the chemoresistance of doxorubicin ( 8 , 9 ). Nevertheless, its role and mechanism in CRC remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Hsa_circ_0006174 acts as miR-138-5p sponge and the followed upregulator of MACC1 (Metastasis-associated in colon cancer protein 1) [ 155 ]. MACC1 is a transcription factor which, via HGF/cMET axis, is involved in EMT in CRC [ 156 ].…”
Section: Oncogenic Functions Of Circrnasmentioning
confidence: 99%